Artificial Intelligence, Human Capital Development And Economic Performance In Saudi Arabia (1990-2019) (Journal of Namibian Studies : History Politics Culture, 2023)
Human capital development and artificial intelligence (AI) are two interconnected concepts that are rapidility gaining traction globally. Thus, this study further examines the relationship between human capital (HC) and economic performance (GDP) using the Artificial Neural Network (ANN) methods to forecast how the GDP would respond to human capital development in Saudi Arabia in the context of Vision 2030. From our findings, GDP plays a major part in establishing a reliable examination with anticipated human capital growth. These results have significant consequences, including comparing the better predictive accuracy of artificial neural network (ANN) studies versus conventional models. Finally, this study offers worldwide policymakers, decision-makers, and company executives insights.